1990
DOI: 10.1111/j.1432-1033.1990.tb19484.x
|View full text |Cite
|
Sign up to set email alerts
|

A highly active and oxidation‐resistant subtilisin‐like enzyme produced by a combination of site‐directed mutagenesis and chemical modification

Abstract: The subtilisins are known to be susceptible to chemical oxidation due to the conversion of Met222 into the corresponding sulfoxide. A number of derivatives with resistance towards oxidation have previously been prepared by replacement of this group with the other 19 amino acid residues. Unfortunately, the activities of these enzymes were of the order of 1 -10% of that obtained with the wild-type enzyme. In contrast, the oxidation-labile cysteine mutant exhibited much higher activity, suggesting that this is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Interestingly, under oxidizing conditions of 0.1 to 1.0 M H 2 O 2 , replacement of Met 222 to non-oxidizable amino acids under these conditions, Ala, Ser or Leu, improved the oxidative tolerance of subtilisin. Based on the fact that the high specific activity of subtilisin is linked to the presence of a sulfur atom at position 222, Breddam and co-workers chemically modified an M222C mutant by thiomethylating the cysteine with the thioalkylating reagent, methyl methane thiosulfonate (Me-MTS) [19]. The engineered thiomethylated subtilisin derivative exhibited an extraordinarily enhanced stability and catalysis under oxidative conditions compared to both wild-type and the unmodified M222C variant during treatment with hydrogen peroxide.…”
Section: Amino Acid Modificationmentioning
confidence: 99%
“…Interestingly, under oxidizing conditions of 0.1 to 1.0 M H 2 O 2 , replacement of Met 222 to non-oxidizable amino acids under these conditions, Ala, Ser or Leu, improved the oxidative tolerance of subtilisin. Based on the fact that the high specific activity of subtilisin is linked to the presence of a sulfur atom at position 222, Breddam and co-workers chemically modified an M222C mutant by thiomethylating the cysteine with the thioalkylating reagent, methyl methane thiosulfonate (Me-MTS) [19]. The engineered thiomethylated subtilisin derivative exhibited an extraordinarily enhanced stability and catalysis under oxidative conditions compared to both wild-type and the unmodified M222C variant during treatment with hydrogen peroxide.…”
Section: Amino Acid Modificationmentioning
confidence: 99%
“…Furthermore, the time-consuming and labor-intensive synthetic procedures have limited application of the chemical modification method. [6][7][8] In contrast to chemical modification, immobilization of enzymes in/on solid supports has offered a simple, alternative, generally requiring one-step reaction. In general, immobilized enzymes show improved stability, making them efficient, reusable and economical.…”
Section: Introductionmentioning
confidence: 99%
“…Previous mutagenesis studies on subtilisin Bacillus amyloliquefaciens (SBA) showed that the methionine sulfur atom next to the catalytic serine (M222 in SBA) was prone to oxidize. The formation of a sulfoxide at this position resulted in enzyme inactivation, probably as a result of destabilization of the transition‐state intermediate . This might be the reason why an inert atmosphere (addition of argon) is required to obtain conversion for the model reaction by using SC.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of as ulfoxide at this position resulted in enzymei nactivation, probably as ar esult of destabilizationo ft he transition-state intermediate. [44][45][46] This might be the reason why an inert atmosphere (addition of argon) is required to obtain conversion for the model reactionb yu sing SC. Estell et al created 19 variants on position M222 in SBA and evaluated the oxygen resistance.…”
Section: Resultsmentioning
confidence: 99%